Association between teriparatide treatment persistence and adherence, and fracture incidence in Taiwan: analysis using the National Health Insurance Research Database. Issue 9 (September 2016) - Chan, D.-C.; Chang, C.; Lim, L.-C.; Brnabic, A.; Tsauo, J.-Y.; Burge, R.; Hsiao, F.-Y.; Jin, L.; Gürbüz, S.; Yang, R.-S.
Abstract Summary Medication persistence and adherence are critical for osteoporosis outcomes. Using the Taiwan National Health Insurance Research Database, we found that persistence and adherence to teriparatide were low in Taiwanese patients with osteoporosis and that greater persistence and adherence were associated with a lower incidence of hip and other nonvertebral fractures. Introduction The purpose of this study was to determine the persistence and adherence to teriparatide treatment in Taiwanese patients with osteoporosis, and to examine the association between persistence and adherence to teriparatide with fracture risks. Methods Medical and pharmacy claims for 4, 692 patients with vertebral or hip fractures and teriparatide prescriptions between 2005 and 2008 were identified (Taiwan National Health Insurance Research Database). Persistence was the time from the start of treatment to the first 90-day gap between two teriparatide prescriptions. Adherence was the number of teriparatide pens (each pen is used over 1 month) prescribed over 24 months. Association of persistence and adherence to teriparatide with fracture incidence was assessed using adjusted Cox proportional hazards models. Results The proportion of patients persisting with teriparatide for >6 months and >12 months was 44.6 and 24.9 %, respectively. Over 24 months, 53.6 % of patients were adherent for >6 months and 33.9 % were adherent for >12 months. Patients persisting for >12 months had a significantly lower incidence of hip (adjusted hazard ratio [HR], 0.61 [95 % confidence interval (CI), 0.40–0.93], P  = 0.0229) and nonvertebral fracture (HR, 0.79 [95 % CI, 0.63–0.99], P  = 0.0462) compared with those who persisted for ≤12 months. Patients adherent for >12 months had a lower incidence of hip (HR, 0.66 [95 % CI, 0.46–0.96], P  = 0.0286) and nonvertebral fracture (HR, 0.81 [95 % CI, 0.66–0.99], P  = 0.0377) compared with those adherent for ≤12 months. Conclusions Persistence and adherence to teriparatide over 24 months were low in Taiwanese patients with osteoporosis; greater adherence and persistence were associated with a lower incidence of nonvertebral fractures.